Visual spatial attention and its impact on the accuracy of the diagonal spike in volleyball - Naji Zwayen, Jinan (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The primary aim of this research was to study visual spatial attention and its impact on the accuracy of the diagonal spike in volleyball. A total of 20 volleyball players of Baghdad participated in this study. The sample was homogeneous in terms of height, weight and age of the players. The tests used in the present study were: 1) Visual Spatial Attention Test. 2) Volleyball Spike Test. Based on the findings of the study, the researcher concluded that visual spatial attention has a significant impact on the accuracy of the diagonal spike in volleyball.